Seroprevalence of Japanese enchephalitis Infection in Pigs in Tulungagung, East Java - Dyah Widiastuti; Tri Wijayanti; Tri Isnani; Nova Pramestuti; Siwi Mars Pramatama Wijayanti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Pigs play a role as amplifier hosts for Japanese enchephalitis (JE). Surveillance of JEV infection on pigs, is, therefore undoubtedly important to prevent its transmission to humans. This study aims to investigate the infection rates of JE in pigs as a risk of JE in human. The study area was located in Tulungagung regency, one of the regencies in East Java with the largest number of pig farms. This was a cross sectional study, involving five pig farms in Tulungagung Regency during April-November 2016, with a total of 63 pigs examined. Venous blood was examined by JEV specific IgG-Enzyme Link Immuno-Sorbent Assay (ELISA). The results showed that the JE infection rates in overall pig samples was 19.05% (12/63). The prevalence of Ab JE in 4-6 month pigs is higher (22.7%) than in 2-3 month pigs. The infections in pigs tend to be higher (23.1%) in farms found to be positive for Culex larvae. Sex and age of the pig and the presence of Culex larvae surround pig farms were not significantly associated with JE infection rates in pigs. In conclusion, the presence of JE virus antibodies in pigs population in Tulungagung indicates that there is a potency of JE virus transmission to humans.